تأجير الأرحام في ضوء الشريعة الإسلامية - محب، محمد منصور (جامعة الأرائك الدولية - مركز البحوث والدراسات, 2024)
بعض أسباب مختلفة يمكن أن تكون سبب مشاكل العقم عند الزوجين. بعض هذه المشاكل على النحو التالي: حركة الحيوان المنوي القليلة، انسداد البوق (الرحمي) أو سوء جودة البويضات، يمكن معالجة هذه الأسباب باستخدام الطرق العلاجية، واستئجار الأرحام هو تقنية طبية حديثة تم تطويرها من طرف الأطباء. أين يدخل في العلاقة الثنائية -بين الزوج وزوجته -طرف ثالث للتمكن من الإنجاب، وذلك عن طريق استعمال رحم امرأة أجنبية -وذلك بسبب عجز الزوجة من حمل طفلها ووضعه بسلام. وعليه فإن عملية استئجار الأرحام، تعتمد على تلقيح بويضة الزوجة بالحيوان المنوي للزوج تلقيحا خارجيا، ثم وضعه في الأنبوب حتى تبدأ البويضة بالانقسام، وتكون مجموعة من الخلايا يتم أخذها وزرعها في رحم امرأة أخرى لينموا في أحشائها إلى غاية ولادته فيسلم للوالدين البيولوجيين، مقابل مبلغ من المال، وفي حالات أخرى يكون الاتفاق على أساس التطوع، معنى هذا أن العملية تتم بدون أي مقابل؛ كأن تحمل المرأة طفل ابنتها، أو أختها، أو صديقتها.... الخ. ومن هنا يطرح الأشكال التالي فما هو حكم الشرعي؟ ما هي الآثار القانونية المترتبة عليه؟ There are various reasons that can cause infertility problems in couples. Some of these problems are as follows: low sperm motility, fallopian tube blockage, or poor egg quality. These causes can be treated using therapeutic methods. Surrogacy is a modern medical technique developed by doctors. Where does a third party enter into the bilateral relationship- between a husband and his wife- in order to be able to procreate, by using the womb of a foreign woman- due to the wife’s inability to carry her child and deliver it safely? Accordingly, the surrogacy process depends on fertilizing the wife’s egg with the husband’s sperm externally, then placing it in the tube until the egg begins to divide, forming a group of cells that are taken and implanted in a woman’s uterus. In other cases, he grows in her womb until he is born and is handed over to the biological parents, in exchange for a sum of money. In other cases, the agreement is on the basis of volunteering, meaning that the process takes place without any compensation. For example, a woman is carrying her daughter’s child, her sister’s child, her friend’s child, etc. From here, the following questions arise: What is the Sharia ruling? What are the legal implications?
Keywords: تأجير الأرحام -- الفقه الإسلامي -- الأحكام الشرعية